Pendidikan pluralisme di Indonesia - rahmawati, Indah putri (Maliki Interdisciplinary Journal, 2026)
This research aims to analyze the urgency, challenges, and implementation strategies of pluralism education in Indonesia as a means of strengthening national integration. As a nation with immense diversity in ethnicity, language, culture, and religion, Indonesia faces real challenges in the form of social polarization and identity politics, which have the potential to undermine national harmony. Employing a qualitative research method with a literature review approach and descriptive analysis, this article examines how educational institutions serve as social models in instilling the values of tolerance. The findings indicate that while Indonesia legally upholds the principle of Bhinneka Tunggal Ika, the implementation of pluralism education faces significant challenges. These include a curriculum that remains too restrictive, limited pedagogical approaches in instilling the values of diversity, and the lingering influence of institutional discrimination. However, implementing the Kurikulum Merdeka (Independent Curriculum) through the Project for Strengthening the Profile of Pancasila Students (Projek Penguatan Profil Pelajar Pancasila or P5) offers significant opportunities to foster universal diversity in a more progressive manner. In conclusion, the success of pluralism education depends not only on a shift in mindset but also on the establishment of a social interaction system involving collaboration between schools, families, the community, and social media. Effective pluralism education is the cornerstone of maintaining national stability and national resilience in the future. Educational change must not stop at the cognitive level alone; rather, it must encompass the emotional and behavioral spheres through communicative discovery.